Longevity-Associated FOXO3 Genotype and its Impact on Coronary Artery Disease Mortality in Japanese, Whites, and Blacks: A Prospective Study of Three American Populations. (30th September 2016) - Willcox, Bradley J.; Morris, Brian J.; Tranah, Gregory J.; Chen, Randi; Masaki, Kamal H.; He, Qimei; Willcox, D. Craig; Allsopp, Richard C.; Moisyadi, Stefan; Gerschenson, Mariana; Davy, Philip M. C.; Poon, Leonard W.; et al.
Abstract: Background: We recently reported that protection against coronary artery disease (CAD) mortality is the major contributor to longer life associated with FOXO3 genotype. The present study examined this relation in more detail. Methods: We performed a 15-year observational study of 3, 584 older American men of Japanese ancestry from the Kuakini Honolulu Heart Program cohort and 1, 595 White and 1, 067 Black elderly individuals from the Health Aging and Body Composition study. Results: Multivariate Cox regression models demonstrated that carriage of the longevity-associated G allele of FOXO3 single nucleotide polymorphisms rs2802292 was a protective factor against CAD mortality in all three populations. In Japanese and Whites, but not in Blacks, the protective effect of the G allele was little changed in models adjusted for other major risk factors. Population-attributable risk (PAR) models found that the nonprotective TT genotype contributed 15%, 9%, and 3% to CAD mortality risk in Japanese, White, and Black Americans, respectively, and was one of the top three contributing factors to CAD mortality. In Japanese, this effect size was comparable with hypertension (15%), but in Whites and Blacks PAR for hypertension was higher (29% and 26%, respectively). G -allele carriers had lower plasma TNF-α than noncarriers, suggesting inflammation as a potential mediating factor for CAD mortality risk. Conclusion: FOXO3 genotype is an important risk factor for CAD mortality in older populations. More research is needed to identify potential mechanisms and targets for intervention.